Overtraining syndrome - what we already know - Bryliński, Łukasz; Woliński, Filip; Duda, Piotr; Drożak, Paulina; Kostelecka, Katarzyna; Baj , Jacek (Journal of Education, Health and Sport, 2022)
Introduction: Overtraining syndrome (OTS) is a state of excess sportsmen's overload caused by too high an intensity of training. The main cause of OTS is too big a training load. Also, they are other risk factors like restrictive diets, inordinate stress, and inflated expectations of a family and a coach. Description of the state of knowledge: despite numerous hypotheses like dysregulation of hypothalamus and pituitary, inflammatory hypothesis, and glycogen hypothesis the exact cause of OTS is not fully understood. None of these hypotheses explains completely all of the symptoms. In diagnosis, several laboratory tests are required to exclude other diseases. After it, because of possible systemic character diagnostic process of OTS is still problematic. One of the diagnostic methods relies on the measurement of hormone levels. Another potential diagnostic method is the measurement of saliva immunoglobulins and other anti-viral proteins. Also, the measurement of serum cell-free DNA can be used. After the onset of OTS, the most important treatment method is rest, which should last for 6-12 weeks or longer. Nowadays, treatment options are looking for shortenings this time. These options are anti-inflammatory drugs and repeated hypoxia-hyperoxia exposure combined with low-intensity training. Since the only well-established treatment method is prolonged rest, prevention is the most important aspect of OTS management. Adequate education of young athletes and their parents is also important. Summary: Overtraining syndrome is a serious problem that concerns many athletes. This problem not only affects results and careers but also sportsmen’s life. Because of the wide scope of symptoms, which can be often nonspecific making the correct diagnosis can be difficult.